PENERAPAN REBUSAN WEDANG JAHE PADA NY. E DENGAN IBU HIPEREMESIS GRAVIDARUMDI DESA SUMBERGEDE TAHUN 2021 - Winda Larasati; Riska Hediya Putri; Eva Yunitasari (Sekolah Tinggi Ilmu Kesehatan Holistik, 2022)
Background: Pregnancy is a physiological and natural process. Hormonal changes on women occur during pregnancy, namely an increase in the hormones progesterone and estrogen. It can cause complaints that will be undergo by pregnant women, one of which is emesis gravidarum. Emesis gravidarum is a common complaint that occurs in early pregnancy. Complementary therapies that can be used to reduce nausea and vomiting in early pregnancy are herbal plants such as ginger. Objective: The objective of this scientific paper is to examine the implementation of wedangjahe decoction on Mrs. E with hyperemesis gravidarumin the first trimester of pregnant woman. Method: The scientific paper design used case study. Respondents used in this study were Mrs. E is the first trimester of pregnant woman who is a client with complaints of hyperemesis gravidarum (nausea and vomiting) in Sumbergede Village. Results: The results of this study showed that after five days of nursing care, Mrs. E the mother who has hyperemesis gravidarum (nausea and vomiting) is resolved. It marked by nausea and vomiting undergo by Mrs. E has decreased. The successful implementation of wedangjahe decoction to reduce nausea and vomiting is influenced by the natural content contained in the ginger plant which has an effect on reducing nausea and vomiting. Conclusion: Conclusion is the implementation of wedangjahe decoction on Mrs. E with hyperemesis gravidarumby using nursing care in accordance with nursing standards for five days, it was found that Mrs. E experienced a decrease in nausea and vomiting after drinking ginger stew. Suggestion for alternatives or recommendations iswedangjahe decoction or it can be replaced by using ginger candy.